Elementary students' reasons for liking or disliking mathematics - Cobacha, Imelda Delfin 1952- (1977)
The study aimed to find out the various reasons of elementary school pupils for liking or disliking mathematics in Grade V and VI of the Divine Word University of Tacloban, Tacloban City, school year 1977-1978. The researcher identified the attitudes of elementary students towards mathematics, the reasons for such attitudes and the implications that the findings may have for teaching and curriculum making. The instruments used were the Attitude Scale Towards Mathematics (Scale Form B) and the Pupils' Questionnaire Checklist. The findings revealed that the attitudes towards mathematics do not vary either according to grade level or between the sexes.